AUTOLOGOUS HEMATOPOIETIC STEM CELL TRANSPLANTATION IN CHILDREN WITH SEVERE RESISTANT MULTIPLE SCLEROSIS - K. I. Kirgizov; E. V. Skorobogatova; R. Ts. Bembeeva; E. Yu. Volkova; A. A. Bologov; S. V. Piliya; A.A. Maschan; A. G. Rumyantsev ("Paediatrician" Publishers LLC, 2013)
Unique experience of high-dose chemotherapy with consequent autologous hematopoietic stem cell transplantation in children with severe resistant multiple sclerosis (n=7) is shown in this article. At present time there is enough data on chemotherapy with consequent hematopoietic stem cell transplantation in children with severe resistant multiple sclerosis. This method was proved to be efficient and safe with immunoablative conditioning chemotherapy regimen. In patients included in this study the mean rate according to the Expanded Disability Status Scale was 5,94±0,2 (from 3 to 9) points. All the patients had disseminated demyelination loci, accumulating the contrast substance, in the brain and the spinal cord. After cyclophosphamide treatment in combination with anti-monocytes globulin the fast stabilization of the condition and prolonged (the observation period was 3-36 moths) clinical and radiologic as well as immunophenotypic remission with marked positive dynamics according to the Expanded Disability Status Scale were noted. No pronounced side-effects and infectious complications were mentioned. The maximal improvement according to the Expanded Disability Status Scale (EDSS) was 5,5 points, the mean - 2,7±0,1 (from 2 to 5,5) points accompanied with positive dynamics on the magneto-resonance imaging.  The efficacy of the treatment was also proved by the positive changes in the lymphocytes subpopulation status in peripheral blood. The timely performed high-dose chemotherapy with consequent hematopoietic stem cell transplantation is an effective and safe method to slowdown the autoimmune inflammatory process. This method can be recommended to use in treatment of children with severe resistant multiple sclerosis.